2015
DOI: 10.1007/s00542-015-2652-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of slots on thermoelastic quality factor of a vertical beam MEMS resonator

Abstract: the resonance occurs in the mechanical domain. MEMS resonators have already started to use in various applications from wrist watches to the state of the art communications, due to their extremely features. However developing a MEMS resonator with high quality factor in MHz frequency ranges, which would be compatible with CMOS integrated circuits (Dragoi et al. 2012) is very important in view of different applications. In integrated circuits, applications such as filters (Bannon et al. 2000;Lopez et al. 2009),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Lengths of the beams are considered to be 30.5 µm, 100 µm, and 400 µm. The place of two outer slots (L as ) is determined based on results of Asadi and Sheikholeslami, 26 where Q TED achieves its maximum amount. The length of these two outer slots (L s1 ) is considered to be 0.1 L b , because for this length, the Q TED increases and the reduction of f res is not a lot.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lengths of the beams are considered to be 30.5 µm, 100 µm, and 400 µm. The place of two outer slots (L as ) is determined based on results of Asadi and Sheikholeslami, 26 where Q TED achieves its maximum amount. The length of these two outer slots (L s1 ) is considered to be 0.1 L b , because for this length, the Q TED increases and the reduction of f res is not a lot.…”
Section: Resultsmentioning
confidence: 99%
“…Their analysis led to an expression for TED in the form of rapidly converging infinite series. Asadi and Sheikholeslami 26 by punching two slots in C–C beam MEMS resonators studied variations of the Q TED and the resonant frequency ( f res ) versus slot places for different slot lengths in 3D case. Their results showed that there are three critical points for f res and Q TED in a C–C beam MEMS resonator, one point is in the middle of the beam and two points are at the anchor-beam interfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having shown how to minimize the by adjusting the orientation of the resonator with respect to the silicon wafer and the doping level, the main goal of this section is to point-out a good strategy to maximize the quality factor of the MEMS resonator. Since it is known from the literature (see e.g., [ 20 , 21 , 22 , 23 ]) that slots may significantly reduce the thermoelastic damping, we now focus on the new model-geometry for a SETF depicted in Figure 9 . Clearly, a multiplicity of slots could be included in the model, but the potentialities of the proposed approach are better put in evidence with a single one.…”
Section: Optimization Of the Tuning Fork Resonatormentioning
confidence: 99%
“…However, the rather low thermoelastic quality factor is a strong limit for practical applications. A known strategy for improving Q consists in adding slots along the beams to reduce heat conduction (see [ 20 , 21 , 22 , 23 ]). Regrettably, slots may also sensibly increase the frequency drift in temperature.…”
Section: Introductionmentioning
confidence: 99%